2021
DOI: 10.1039/d1sc02695j
|View full text |Cite
|
Sign up to set email alerts
|

Rational generation of lasso peptides based on biosynthetic gene mutations and site-selective chemical modifications

Abstract: Lasso peptides are a unique family of natural products whose structures feature a specific threaded fold, which confers these peptides the resistance to thermal and proteolytic degradation. This stability gives...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Natural stlassin is a class II lasso peptide without any extra PTMs (Figure 2a). Double cysteine mutant variants Val2Cys/Ala11Cys and Val3Cys/Pro12Cys produced two stlassin derivatives with disulfide bonds positioned between the macrolactam ring and the Cterminal loop, creating a type of lasso fold that is outside the traditional four classes [24]. Notably, these derivatives support that disulfide bonds in lasso peptides might form spontaneously, consistent with the findings from class I and IV lasso peptides.…”
Section: Disulfurationsupporting
confidence: 76%
See 1 more Smart Citation
“…Natural stlassin is a class II lasso peptide without any extra PTMs (Figure 2a). Double cysteine mutant variants Val2Cys/Ala11Cys and Val3Cys/Pro12Cys produced two stlassin derivatives with disulfide bonds positioned between the macrolactam ring and the Cterminal loop, creating a type of lasso fold that is outside the traditional four classes [24]. Notably, these derivatives support that disulfide bonds in lasso peptides might form spontaneously, consistent with the findings from class I and IV lasso peptides.…”
Section: Disulfurationsupporting
confidence: 76%
“…), antiviral activities (e.g., MS-271, specialicin [14], etc.) and receptor antagonistic activity (e.g., stlassin [24]), lasso peptides have attracted much attention during the past few years with a notably increasing number of RiPPs of this subclass.…”
Section: Discussionmentioning
confidence: 99%
“…While changes to the isopeptide-bonded residues are generally not tolerated for lasso peptides, , several reports demonstrated that certain biosynthetic enzymes could tolerate variations at these positions. ,, For cloacaenodin, G1A and E9D variants were not produced, as the variants could not be detected in the supernatant or the cell pellet.…”
Section: Resultsmentioning
confidence: 99%
“…Several mutantvariants of stlassin, including I4A, I4C, F15Y, and the chemically modified I4C and F15Y (I4C−III and F15Y−I) exert comparable inhibitory activities, in which F15Y and F15Y−I display smaller IC 50 values than the native peptide. 168 Atropopeptides (atropitides) are a new family RiPPs with only four members identified up to now: tryptorubin A and B from Streptomyces sp. CLI2509 and amyxirubin A and B from Amycolatopsis xylanica (Figure 25).…”
Section: Ripps With Other Biological Activitiesmentioning
confidence: 99%
“…PKUMA01240 shows no antimicrobial, antitumor, or antivirus activity but antagonistic activity against the binding of lipopolysaccharides (LPS) to toll-like receptor 4 (TLR4), which may be used for preventing or treating inflammatory diseases. Several mutant-variants of stlassin, including I4A, I4C, F15Y, and the chemically modified I4C and F15Y (I4C–III and F15Y–I) exert comparable inhibitory activities, in which F15Y and F15Y–I display smaller IC 50 values than the native peptide …”
Section: Ripps With Other Biological Activitiesmentioning
confidence: 99%